STUDY OF THE TERMIZ LITERARY SCHOOL - Jamahmatov Karomiddin Aynillo oglu (Modern American Journals, 2025)
This article discusses the historical processes of the Termiz literary school, as well as the poets of Termiz origin who were creatively active during the 13th-19th centuries.
Keywords: Termiz, literary school, city of heroes, Chaghaniyon, literature, mysticism, science and enlightenment.